Analysis of the Imposition of Export Tax on Indonesian Cocoa Beans: Impact on the Processed Cocoa Export Indonesia and Malaysia - Yudyanto, Hendy; Hastiadi, Fithra Faisal (International Journal of Economics and Financial Issues, 2017)
This research aims to observe the impact of the export tax tariff imposition on Indonesian cocoa beans against the export of processed cocoa products from Indonesia and Malaysia in the long-term. Research variables used are the export volume of processed cocoa products in Indonesia and Malaysia, price of Indonesian cocoa beans, price of international cocoa beans, average price of processed cocoa exports in five competitor countries of Indonesia and Malaysia, volume of processed cocoa imports worldwide and the dummy application of the Indonesian cocoa export tax. In response to the research objectives, the Autoregressive Distributed Lag (ARDL) and the bound testing co-integration methods are applied in observing the co-integration of variables researched. Data analyses outcomes indicate that the imposition of export tax on Indonesian cocoa beans significantly affect the increased export volume of the Indonesian processed cocoa in the long-term. Meanwhile, for Malaysia, the imposition of export tax on the Indonesian cocoa beans does not significantly affect decreased export volume of Malaysian processed cocoa in the long-term. Keywords: Export Tax, Cocoa Beans, Export, Processed Cocoa, ARDL JEL Classifications: F13; L66